Proceedings of the Linguistic Annotation Workshop on - LAW '07 2007
DOI: 10.3115/1642059.1642083
|View full text |Cite
|
Sign up to set email alerts
|

Standoff coordination for multi-tool annotation in a dialogue corpus

Abstract: The LUNA corpus is a multi-lingual, multidomain spoken dialogue corpus currently under development that will be used to develop a robust natural spoken language understanding toolkit for multilingual dialogue services. The LUNA corpus will be annotated at multiple levels to include annotations of syntactic, semantic, and discourse information; specialized annotation tools will be used for the annotation at each of these levels. In order to synchronize these multiple layers of annotation, the PAULA standoff exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…In order to make the subsequent processing easier and the form of the transcribed files The Rovereto Emotion and Cooperation Corpus 123 more uniform, we adopted the conventions of the LUNA corpus (Rodríguez et al 2007). Two transcribers fixed the problems in each orthographic transcription and run a validation script to find unrecognized spelling and transcription codes.…”
Section: Transcription Methodsmentioning
confidence: 99%
“…In order to make the subsequent processing easier and the form of the transcribed files The Rovereto Emotion and Cooperation Corpus 123 more uniform, we adopted the conventions of the LUNA corpus (Rodríguez et al 2007). Two transcribers fixed the problems in each orthographic transcription and run a validation script to find unrecognized spelling and transcription codes.…”
Section: Transcription Methodsmentioning
confidence: 99%
“…Recently, several studies have addressed multilevel annotation of dialogues [1,12,15]; in our study, we focus on the two aspects of a DA indicated by [4]. One is the communicative function that corresponds to how the content should be used in order to update the context, and the other is a semantic content that corresponds to what the act is about.…”
Section: Annotation Of Communicative Function and Semantic Con-tent Imentioning
confidence: 99%
“…In this study, we adopt dialogue acts (DAs) [1,4,12,15,16] for this information and annotate DAs in the corpus.…”
Section: Poster Sessionmentioning
confidence: 99%
“…Recently, several studies have addressed multilevel annotation of dialogues (Levin et al, 2002;Bangalore et al, 2006;Rodriguez et al, 2007); in our study, we focus on the two aspects of a DA indicated by Bunt (2000). One is the communicative function that corresponds to how the content should be used in order to update the context, and the other is a semantic content that corresponds to what the act is about.…”
Section: Annotation Of Communicative Function and Semantic Content In Damentioning
confidence: 99%
“…In this study, we adopt dialogue acts (DAs) (Bunt, 2000;Shriberg et al, 2004;Bangalore et al, 2006;Rodriguez et al, 2007;Levin et al, 2002) for this information and annotate DAs in the corpus.…”
Section: Introductionmentioning
confidence: 99%